Efeitos dos treinamentos funcional e tradicional na composição corporal, determinantes da aptidão física e qualidade dos padrões de movimento em idosas: um ensaio clínico randomizado e cruzado - Resende Neto, Antonio Gomes de (2021)
Introduction: Functional training (FT) emphasizes general conditioning exercises aimed at improving neuromuscular efficiency for the individual's daily needs. On the other hand, traditional training (TT) aims to improve muscle fitness, through exercises predominantly performed on machines. Lately, there is a lack of investigations comparing and integrating FT with TT methods to better observe the real effects on multisystem adaptive responses. Objective (Experiment 1): To analyze the efficacy and integration of functional and traditional training in body composition, determinants of physical fitness and quality of movement patterns in older women. Objective (Experiment 2): To determine whether functional training has effects similar to traditional training on body composition and muscle strength components in physically active older women. Methods: This is a randomized and crossover clinical trial, allocating 48 physically active older women into three groups: 1st- Program that started with FT and ended with TT (FT→TT: n=13), 2nd- Program that started with TT and ended with FT (TT→FT: n=19) and 3rd - Stretching Group (SG: n=16). Participants trained 24 weeks, three weekly sessions lasting 45-50 min each. Body composition was assessed using bioimpedance, physical/functional fitness with the Senior Fitness Test battery and the quality of movement patterns using the Functional Movement Screen®. In addition, maximum dynamic force (MDF) was verified through the 1RM test on the leg press and row machines. For analysis of muscle power (MP), 50% of the maximum load was used and speed was determined using a linear encoder and the isometric force (IF) with dynamometers, manual and lumbar. All variables were analyzed at baseline and after 12 weeks of follow-up at each stage of the study using two distinct data plots (grouping conventional crossover and/or integrative). Results (Experiment 1): Compared to SG, both TT→FT and FT→TT integration promoted a significant improvement in dynamic balance/agility (p = 0.012; 13.60% and p = 0.007; 13.06%, respectively) and upper limb strength (p <0.001; 24.91% and p = 0.011; 16.18%). Considering the adaptations of the methods separately from the conventional cross-over grouping, only the FT showed a statistically significant improvement in the strength of the lower limbs (p = 0.001), cardiorespiratory capacity (p = 0.003) and quality of the movement patterns when compared to the SG (p = 0.030). Results (Experiment 2): FT showed a significant decrease in the percentage of fat (p = 0.015; Δ%: 3.51) and TT significantly increased lean mass (p = 0.008; Δ%: 2.92). Both FT and TT generated significant increases in MDF, MP and IF compared to the initial values and SG, which showed declines in these variables. There were no statistically significant differences between the experimental groups in body composition and muscle strength components. Conclusion: In view of the sample and the conditions analyzed, functional and traditional training are equally effective in improving the components of muscle strength and other determinants of physical fitness in older women, so they can be complementary to combat some of the deleterious effects of senescence.